Mechanical performance of monolithic materials cemented to a dentin-like substrate - Weitzel, Isabela S.S.L.; Rangel, João H.R.; Perim, Magna P.; Melo, Renata M. [UNESP]; Borges, Alexandre L.S. [UNESP]; Silva-Concílio, Laís R.; Amaral, Marina (My University, 2020)
Statement of problem: Studies on the mechanical behavior of restorative materials bonded to tooth structure and considering the properties of the material and the bonding between both substrates are lacking. Purpose: The purpose of this in vitro study was to evaluate the hardness, fracture toughness, load-to-failure, cyclic fatigue, and stress distribution of 4 computer-aided design and computer-aided manufacturing (CAD-CAM) materials when bonded to a substrate similar to dentin (G10). Material and methods: Disks (11×1.2 mm) of lithium disilicate (LD), feldspathic ceramic (FC), polymer-infiltrated ceramic (PC), and a nanohybrid composite resin (NC) were fabricated (n=45) and had their surfaces polished. Microhardness was measured by the Knoop indentation (19.61 N, 12 seconds, n=5). Indented specimens were subjected to biaxial flexural strength testing, and the fracture origin defect was measured to calculate fracture toughness (n=5). Forty disks from each material were adhesively bonded to G10. Half of the specimens were subjected to load-to-failure testing, and remaining specimens (n=20) were subjected to cyclic fatigue (400 N, 106 cycles). The test was suspended every 200 000 cycles, and specimens were examined for cracks, debonding, or catastrophic failure. Obtained data were evaluated by analysis of variance and the Tukey post hoc test (α=.05). Weibull analysis was also performed. A 3D model of the tested specimens was constructed in a design software program, and the stress distribution was evaluated by finite element analysis, with the application of a 100-N load normal to the restoration surface. Results: Hardness values with statistically significant differences were LD (540.4)>FC (474.6)>PC (176.6)>NC (58.26). Fracture toughness vales (MPa.m1/2) and statistical significance were as follows: LD (2.25)=NC (2.46)>FC (1.14)=PC (1.18). Load-to-failure values (N) were LD (2881.6)=FC (2881.6)=PC (3200.6)>NC (2367.5). A specimen each of LD and NC fractured during the fatigue test, and LD and PC had a high percentage of subsurface cracks (55% and 75%, respectively). The FC had the lowest debonding rate after load-to-failure testing and no catastrophic fractures or cracks during fatigue. Conclusions: The materials tested had different mechanical behaviors depending on the tests performed. Feldspathic ceramic had the best fatigue behavior when cemented to a dentin-like substrate.